Comparisons of commercial frozen yogurt with KSU formulation - J.H. Kim; I.J Jeon; M.S. Forbes; Karen A. Schmidt (Kansas Agricultural Experiment Station Research Reports, 1995)
Ten samples of vanilla frozen yogurt were purchased in Kansas and compared to a highprotein, KSU formulation. The KSU formulation had similar solids, fat, and sugar contents as the commercial samples. All commercial samples had lower protein (almost less than half) content and more lactose, and almost all samples had fewer lactic acid bacteria than the KSU formulation. All but one commercial sample had lower b-galactosidase activity than the KSU formulation. This may reflect the differing lactic acid bacterial populations in the frozen yogurts.; Dairy Day, 1995, Kansas State University, Manhattan, KS, 1995;
Keywords: Dairy Day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-106-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 742; Frozen yogurt; Lactic acid; Bacteria; Microbial Quality